A comparison of methods for staining tubercle bacilli in histological sections. Issue 4 (April 1973) - Greenwood, N.; Fox,; H.
Abstract : The Ziehl-Neelsen stain is compared with three alternative methods of staining tubercle bacilli in paraffin sections: Fite's method (1938); a modification by Armstrong and Price (1947) of Fite's method; and a fluorescent method using the auramine-phenol stain. The fluorescent method was found to be the most effective of the four methods and its use is recommended as a routine tool in diagnostic histopathology.